2018
DOI: 10.1016/j.chemosphere.2018.02.107
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of biotransformation, sorption, and desorption of multiple chemical contaminants in pilot-scale drinking water biofilters

Abstract: The evolving demands of drinking water treatment necessitate processes capable of removing a diverse suite of contaminants. Biofiltration can employ biotransformation and sorption to remove various classes of chemicals from water. Here, pilot-scale virgin anthracite-sand and previously used biological activated carbon (BAC)-sand dual media filters were operated for ∼250 days to assess removals of 0.4 mg/L ammonia as nitrogen, 50-140 μg/L manganese, and ∼100 ng/L each of trace organic compounds (TOrCs) spiked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 59 publications
4
32
0
2
Order By: Relevance
“…In accordance with these results, other studies also observed better removal of biodegradable organic matter on BAC than on non-adsorptive filter materials. [34][35][36] Multiple explanations for the benefits of BAC have been reported. The porous structure of GAC media provides a significantly higher specific surface area and increased roughness of the surface, compared with compact grains of anthracite or sand.…”
Section: Organic Bulk Parametersmentioning
confidence: 99%
“…In accordance with these results, other studies also observed better removal of biodegradable organic matter on BAC than on non-adsorptive filter materials. [34][35][36] Multiple explanations for the benefits of BAC have been reported. The porous structure of GAC media provides a significantly higher specific surface area and increased roughness of the surface, compared with compact grains of anthracite or sand.…”
Section: Organic Bulk Parametersmentioning
confidence: 99%
“…The majority of the studies evaluated used GAC as the biological filtration media, although a number of facilities also used other media such as sand and anthracite. Previous studies have shown that vastly different microbial populations were developed in different media, with carbon‐based media exhibiting greater microbial diversity, potentially impacting BAF performance (Gerrity et al, 2018; Greenstein, Lew, Dickenson, & Wert, 2018; Vignola, Werner, Wade, Meynet, & Davenport, 2018). The impact of media type on CEC removal in this study was assessed through comparison of selected CEC along the treatment train of two full‐scale facilities using different media type but similar O 3 :TOC ratio (0.5–0.65 mg O 3 /mg TOC): project J used anthracite in their BAF system, while project K used GAC.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that, in addition to the factors mentioned above, BAF performance is also influenced by media age and backwashing frequency (Arnold et al, 2018; Sundaram et al, 2020), as well as acclimation periods (Greenstein et al, 2018, p. 47; Zearley, 2012, p. 170). The effect of media age is especially important when using GAC as the contaminant removal will transition from carbon‐based to mixed carbon to noncarbon‐based (e.g., biodegradation, adsorption to biofilms) and finally to full biodegradation at approximately 20,000 bed volumes (BVs) based on a study conducted by Sundaram et al (2020).…”
Section: Resultsmentioning
confidence: 99%
“…Desorption of a compound indicates that it was previously removed by adsorption and not biodegradation. Sundaram and Pagilla (2019) showed that more than 90% of sucralose was removed by adsorption onto GAC media, while Greenstein et al (2018) did not report removal of sucralose as the GAC media was already exhausted. Cotinine is poorly removed by ozone and biodegradation and has shown to breakthrough in an 18‐min EBCT GAC at 12,500 BV (Kennedy, Reinert, Knappe, Ferrer, & Summers, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The removal of certain CECs, such as N,N-Diethyl-meta-toluamide (DEET), naproxen, and ibuprofen, has been shown to be improved with a higher EBCT of 14 min compared to 5 min in biofilters containing anthracite (Hallé, Huck, & Peldszus, 2015), demonstrating that these compounds are primarily removed by biodegradation. There are other studies showing the importance of BAC in the biodegradation of CECs (Abromaitis, Racys, van der Marel, & Meulepas, 2016;Greenstein, Lew, Dickenson, & Wert, 2018;Nugroho, Reungoat, & Keller, 2010). Furthermore, although GAC units are intended to sorb CECs, in fact, they will be readily colonized by microorganisms that could also contribute to CEC removal (Rattier, Reungoat, Gernjak, Joss, & Keller, 2012).…”
Section: Introductionmentioning
confidence: 99%